Protection Elements for Safflower Oilseeds - Ivanchenko , Tatyana; Belikina, Anna (KnE Life Sciences, 2021)
Agricultural techniques for growing safflower, adaptive to the natural and climatic zone, is an important and necessary measure for increasing yields and improving the quality of oil seeds of safflower (Carthamus tinctorius L). Biological and morph physiological characteristics of the culture and its variety determine the technological methods for its cultivation and production of oil seeds. Safflower is a crop that is of great value and is able to replace sunflower. The agricultural technology of its cultivation in the Lower Volga region is constantly being studied; however, safflower plant protection methods are not well understood. Experiments to study the effectiveness of safflower protection methods were carried out in 2017-2019 on the territory of the experimental field of the Federal Research Center for Agro-Ecology of the Russian Academy of Sciences, where light chestnut soils with a humus content of 1.2-2.0% and pH = 7.8 predominate. Ways of protecting safflower were considered and the effectiveness of seed dressing with a mixture of Vincit 1.5 l/t + Fertigrain Start 0.5 l/t was revealed. This option was the most profitable (16.5%), with a yield of 1.2 t/ha. The control option using a mixture of Vincit + Azotovit + Phosphatovit 1.5 l/t + 2.2 l/t + 2.2 l produced a yield of 0.8 t/ha and was not profitable. Keywords: agricultural technology, safflower, productivity, oil content of seeds, plant protection, root rot, pesticides, agrochemicals